Terpenylated coumarins from the root bark of Ailanthus altissima (Mill.) Swingle. (July 2020) - Yan, Zhi-Yang; Lv, Tian-Ming; Wang, Yu-Xi; Shi, Shao-Chun; Chen, Jing-Jie; Bin-Lin,; Liu, Qing-Bo; Huang, Xiao-Xiao; Song, Shao-Jiang
Abstract: Seven undescribed terpenylated coumarins, named altissimacoumarin I–O, together with seven known compounds, altissimacoumarin C, altissimacoumarin E, altissimacoumarin G, altissimacoumarin H, puberulin, 7-(3-Methyl-2-butenyloxy)-6-methoxycoumarin and artelin were isolated from the root bark of Ailanthus altissima (Mill.) Swingle. Their structures were elucidated by comprehensive spectra data analysis, NMR calculation, DP4+ analysis and ACD/Structure Elucidator software simulation. The absolute configurations of altissimacoumarins K, L, M and N were determined by modified Mosher's method. All isolates were tested for their cytotoxic effect against two hepatoma carcinoma cell lines (HepG2, Hep3B). Altissimacoumarin C exhibited moderate cytotoxic effect against Hep3B cells, with IC50 of 45.21  μ M. Graphical abstract: Image 1 Highlights: Seven previously undescribed terpenylated coumarins were isolated and identified. NMR calculation, DP4+ analysis and ACD/Structure Elucidator were used for structure validation. The absolute configurations of some isolates were determined by Mosher's method and NOESY experiment. Structure revision of altissimacoumarin E is proposed.